Neolithic occupation and stone working on the Yorkshire Wolds - Pouncett, J (2019)
This thesis explores the evidence for Neolithic occupation and stone working on the Yorkshire Wolds based on stray finds and lithic scatters from surface contexts. Traditional models for Neolithic occupation are based largely on evidence from excavated contexts, in particular the groups of Neolithic pits at Rudston, and Neolithic houses on the Holderness coast. Extensive scatters of worked flint, however, have been identified on the Yorkshire Wolds. These scatters have not been incorporated into accounts of Neolithic occupation for two reasons: 1) the lithic scatters are typically characterised by low-densities of artefacts, and; 2) the scatters typically contain few artefacts which are typologically diagnostic. A methodology that addresses both of these problems was developed, using: 1) an implementation of Tobler’s resel-based GIS to apply focal functions/spatial filters to polygon features in order to identify spatial patterning in survey data characterised by low-densities of artefacts, and; 2) a method for assigning dates to stone tools and lithic debitage using artefact scores based on diagnostic traits identified through the analysis of lithic assemblages from excavated contexts. The methodology was developed using case studies drawn from a study area centred on the parish of Fimber that had previously been investigated in the nineteenth century by J.R. Mortimer. Analysis of lithic assemblages from sixteen of the Neolithic burial mounds excavated by Mortimer and a surface scatter at Wharram-le-Street close to the former source of the Gypsey Race was carried out. This analysis indicates that traditional models of Neolithic occupation based on a distinction between the High Wolds and Low Wolds cannot be sustained on the basis of evidence from surface contexts and that Neolithic stone working traditions on the Yorkshire Wolds were constrained by the nature of the raw materials available to local communities.